Unconventional Non‐Aqueous Emulsions for the Encapsulation of a Phototriggerable NO‐Donor Complex in Polymer Nanoparticles. (5th February 2013) - Bohlender, Carmen; Landfester, Katharina; Crespy, Daniel; Schiller, Alexander
<x xml:space="preserve">Abstract</x> A non‐aqueous emulsion system with hexafluoroisopropanol (HFIP) provides nanoparticles from gelatin, polylactide, poly(vinyl formal), and poly(ethylene terephthalate). Poly(vinyl formal) particles can embed a ruthenium nitrosyl complex for phototriggered NO release. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>